Current Situation of Agricultural Product Export Financing and its Analysis - Tajenova Gulbakhar Esbosynovna; Abishov Muhammed Sarsenbaevich; Kallibekov Allabergen Saparbaevich (Periodica Journal, 2022)
The article mainly talks about the current state of agricultural export financing today and the importance of analyzing it.
Keywords: Agriculture; financing; export; import